The Effectiveness of Islamic Religious Education Learning on Students' Morals at Pelita Pesawaran Lampung Vocational School - Umi Rohimatun Nangimah; Mispani Mispani; Saidun Anwar (International Journal on Advanced Science, Education, and Religion, 2024)
This research discusses educational issues, especially the declining morality of students in Indonesia. Crime, promiscuity, violence against children and sexual harassment are increasing, tarnishing the image of students and educational institutions. This research aims to understand the effectiveness of Islamic religious learning on the morale of students at SMK Pelita Pesawaran. Qualitative methods are used to understand this phenomenon, with direct observation, interviews, and inductive data analysis. Teachers prepare lessons well, pay attention to students' seating arrangements, choose appropriate learning resources and media, and carry out learning and evaluation carefully. The conclusion of this research shows that PAI learning is effective but has not yet reached its maximum potential, with the role of teachers, students and infrastructure as supporting factors. The approaches used by teachers vary, but the humanistic approach seems to be the most conducive to student morale Keywords: Student Morality, Effectiveness of Islamic Religious Learning, Classroom Management